1992
DOI: 10.1007/bf00004652
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for tryptophan by milkfish (Chanos chanos Forsskal) juveniles

Abstract: Groups of milkfish juveniles (mean initial weight 7.7 g) were fed semipurified diets containing 0.9, 1.4, 2.1, 3.1, 4.1 and 6.1 g tryptophan/kg dry diet for 12 weeks. The mean crude protein content of the diets (containing white fishmeal, gelatin and free amino acid mixture to simulate the pattern of hydrolysed milkfish protein) was 49%. On the basis of the growth response, the tryptophan requirement of milkfish juveniles was estimated to be 3.1 g/kg diet. Fish fed low levels of tryptophan exhibited low weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
(32 reference statements)
2
13
0
Order By: Relevance
“…However, these symptoms were not seen in tryptophan-deficient catfish (Wilson et al 1978). Coloso et al (1992Coloso et al ( , 2004 reported impaired growth and low feed conversion in milkfish and Asian sea bass, fed tryptophandeficient diet. High incidence of skeletal deformities, especially at vertebral column in white seabream, Diplodus sargus, was also reported in fish fed tryptophan-deficient diets by (Saavedra et al 2006a, b).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, these symptoms were not seen in tryptophan-deficient catfish (Wilson et al 1978). Coloso et al (1992Coloso et al ( , 2004 reported impaired growth and low feed conversion in milkfish and Asian sea bass, fed tryptophandeficient diet. High incidence of skeletal deformities, especially at vertebral column in white seabream, Diplodus sargus, was also reported in fish fed tryptophan-deficient diets by (Saavedra et al 2006a, b).…”
Section: Discussionmentioning
confidence: 90%
“…The dietary tryptophan requirement has been worked out for a limited number of cultured fish species such as sockeye salmon Oncorhynchus nerka (Halver 1965), channel catfish (Wilson et al 1978;Ng et al 1997), rainbow trout (Poston and Rumsey 1983;Walton et al 1986;Kim et al 1987), gilthead sea bream Sparus aurata (Luquet and Sabaut 1974;Kaushik 1998), milk fish (Coloso et al 1992), Indian major carp Labeo rohita (Murthy and Varghese 1997), African catfish Clarias gariepinus (Fagbenro and Nwanna 1999), Asian sea bass Lates calcarifer (Coloso et al 2004), hybrid striped bass Morone chrysops x M. saxatilis (Gaylord et al 2005), and an other Indian major carp, mrigal (Ahmed and Khan 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As in milkfish, chinook salmon, and channel catfish fed tryptophan‐deficient diets (Wilson et al., 1978; Coloso et al., 1992), no gross nutritional deficiency signs were observed in sea bass given low dietary tryptophan except for growth depression. In contrast, gross deformities such as scoliosis, lordosis, eye cataracts, short gill opercula and caudal fin erosion have been reported for rainbow trout or chum salmon juveniles fed tryptophan‐deficient diets (Kloppel and Post, 1975; Poston and Rumsey, 1983; Walton et al., 1984a; Akiyama et al., 1986) and were prevented by the addition of tryptophan to the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Little difference was found, whether exponential or saturation kinetics approach was used in estimating the requirement (Rodehutscord and Pack, 1999). In addition, the tryptophan requirement of milkfish Chanos chanos Forsskal, a euryhaline tropical fish, has been estimated to be 3.1 g kg −1 diet (0.6% of protein) (Coloso et al., 1992). Tryptophan deficiency results in scoliosis, lordosis, eye cataracts, and increased liver and kidney levels of Ca, Mg, Na, and K (Walton et al., 1984a), and about 0.6 g tryptophan (100 g protein) −1 is required to obtain pathology‐free trout (Poston and Rumsey, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ingredients used for formulation of artificial feeds are limiting in four major essential amino acids (Ahmed, ). Besides lysine, methionine and threonine, tryptophan is one of the most limiting amino acids in plant proteins with high potential for use in fish diets such as corn meal and wheat germ meal (Coloso, Murillo‐Gurrea, Borlongan, & Catacutan, ; Coloso, Tiro, & Benitez, ). Tryptophan is a structural component of proteins and could promote protein synthesis and deposition, which is important for fish growth (Sidransky, Murty, & Verney, ; Tang et al., ).…”
Section: Introductionmentioning
confidence: 99%